Kinetics of Plasma Cytokines During Two Different Modalities of Extracorporeal Blood Purification in the Critically Ill Covid 19 Patients: A Cohort Study - Ponce, Daniela [UNESP]; Zamoner, Welder [UNESP]; Magalhães, Luis Eduardo [UNESP]; de Oliveira, Paula Gabriela Sousa [UNESP]; Polla, Patricia [UNESP]; Barbosa, Alexandre Naime [UNESP]; de Assis Golim, Marjorie [UNESP]; Snr, André Luís Balbi [UNESP] (Taylor & Francis, 2022)
Background: In the absence of direct therapy for COVID-19, extracorporeal blood treatment (EBT) could represent an option for cytokine removal. Objective: This study aimed to describe and compare cytokine removal during intermittent haemodialysis (IHD) and continuous renal replacement therapy (CRRT) in COVID-19 patients with Acute Kidney Injury (AKI). Methods: It was a cohort study that studied patients with COVID-19-related AKI according to KDIGO criteria and admitted at Intensive Care Unit (ICU). Blood samples were collected at the start and end of both IHD using high flux (HF) membranes (10 patients) and continuous venovenous haemodiafiltration (CVVHDF:10 patients) in two sessions for measuring 13 different plasma interleukins and calculating the cytokine removal rate. Results: There was no difference between the two groups regarding mechanical ventilation, vasoactive drug, age or prognostic scores. Patients treated by CRRT presented higher levels of IL-2 and IL-8 than patients treated by IHD at dialysis start. Cytokine removal ranged from 9% to 78%. Patients treated by CRRT presented higher cytokine removal for IL-2, IL-6 IL-8, IP-10 and TNF. The removal rates of IL-4, IL-10, IL-17A, IFN, MCP-1 and TGF-B1 were similar in two groups. After one session of CVVHDF (24 h), IL-2 and IL-1β levels did not vary significantly, whereas IL-4, IL-6, IL-8, IL-10, IL-17A, TNF, IFN, IP-10, MCP-1, IL-12p70 and TGF-B1 decreased by 33.8–76%, and this decrease was maintained over the next 24 h. In IHD groups, IL-2, IL-6, TNF, IP-10 and IL-1β levels did not decrease significantly whereas IL-4, IL-8, IL-10, IL-17A, IFN, MCP-1, IL-12p70 and TGF-B1 decreased by 21.8–72%; however, cytokine levels returned to their initial values after 24 h. Conclusion: Cytokine removal is lower in IHD using HF membranes than in CVVHDF, and in IHD the removal is transient and selective, which can be associated with mortality during cytokines storm-related COVID-19.
Keywords: cytokine storm; EBP; removal